Perencanaan Komunikasi Program Ojek Makanan Balita (Omaba) Dalam Membentuk Persepsi Orang Tua Mengenai Anak Gizi Buruk (Studi Deskriptif Pada Orang Tua Dengan Riwayat Anak Gizi Buruk Di Kelurahan Cisaranten Kidul, Gede Bage): Nancy Citra Purnaningtyas, Nofha Rina - Nancy Citra Purnaningtyas; Nofha Rina (Prodi Ilmu Komunikasi Universitas Putera Batam, 2018)
Nowadays malnutrition is one of big problem that still being a government concern in health sector. At Gede Bage Bandung City on 2013 there are 29 cases of malnutrtion founded, 17 cases of them is at Cisaranten Kidul which is under the responsibility of Riung Bandung Public Health Center. Riung Bandung Public Health Center has succeeded in doing an innovation of health program called Ojek Makanan Balita (OMABA) which able to reduce malnutrition rate. The purpose of this research is to know the communication planning of OMABA program in shaping the perception of parents with children who have history of malnutrition in Cisaranten Kidul. The method used in this research is descriptive qualitative method by using in-depth interview technique which also supported with documentation obtained from Riung Bandung Public Health Center. The result of this research is that communication planning in OMABA program has been implemented systematically and structured and this program is able to form a perception to the participants that eat healthy food and that healthy food does not have to be expensive.